Ballot order effects: An analysis of Irish General Elections - John Regan (University College Dublin, UCD School of Economics, 2012)
This paper presents evidence of ballot order effects in Irish General Elections, where candidates are listed in alphabetical order. Data relating to elections from 1977 to 2011 suggest the effect is significant in a statistical sense and in magnitude. The nature of the Irish electoral system sees voters cast preferences for candidates, and as a result a greater level of information regarding voters becomes available. Various fixed effects are added to control for constituencies, candidates and political parties.
Keywords: 330